An investigation of the metaphoric potential of the relationship between pictorial and sculptural space - Penfold, Denise Marcelle (Michaelis School of Fine Art, 2024)
The aim of this dissertation is to provide a background to the ideas and works that have informed the practical body of work. The practical body of work has developed from an intention to locate a means of articulating personal experience in visual form. The departure points for this process are thus largely idiosyncratic and personal (subjective), while the focus of the investigation is on the potential for the dialectic of pictorial/physical space to articulate metaphors that can mediate personal experience. This dialectic of pictorial/physical space can be related to one of the primary philosophical debates that underpins Western art practice and theory; viz., the relationship between art and reality, or in other terms, between culture and nature.